KING ASHUR RISH-ISHI I - AL-MUSAWI, SARAH ABDULAH AATI; ABDULMALEK, MUNTHER ALI (Al-Adab Journal, 2023)
This research sheds light Resume King, Ashur Rish-Ishi I is considered one of the most prominent royal Figures in the Assyrian middle eras. The dynasty of this king was beginning of Assyrian role in decline and the end of decline and powerlessness Coming after the death of King Tokiti Nanorta 1. well as well eat percentage of The Coronation of the king hisnick name his family.